2013
DOI: 10.1088/1674-1056/22/5/050301
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and experimental measurement of the electromagnetic thrust generated by a microwave thruster system

Abstract: A microwave thruster system that can convert microwave power directly to thrust without a gas propellant is developed. In the system, a cylindrical tapered resonance cavity and a magnetron microwave source are used respectively as the thruster cavity and the energy source to generate the electromagnetic wave. The wave is radiated into and then reflected from the cavity to form a pure standing wave with non-uniform electromagnetic pressure distribution. Consequently, a net electromagnetic thrust exerted on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…The theory was applied in cosmological [4] and galactic [5] contexts, and in [3] it was used to explain the discordant measurements of Newton gravitational constant as due to the effect of the earth's magnetic field. In [1] it was further shown that a ST theory of the MLR type could explain the unusual forces on asymmetric resonant cavities reported at that time [6]. However, in the derivation of the equations from the action principle some inconsistencies were observed, and also the forces obtained, after reconsideration of the experiments originally reported and new results [2], were too high.…”
Section: Introductionmentioning
confidence: 91%
“…The theory was applied in cosmological [4] and galactic [5] contexts, and in [3] it was used to explain the discordant measurements of Newton gravitational constant as due to the effect of the earth's magnetic field. In [1] it was further shown that a ST theory of the MLR type could explain the unusual forces on asymmetric resonant cavities reported at that time [6]. However, in the derivation of the equations from the action principle some inconsistencies were observed, and also the forces obtained, after reconsideration of the experiments originally reported and new results [2], were too high.…”
Section: Introductionmentioning
confidence: 91%
“…Independent tests were carried out in China by Yang et al [10][11][12] who tested the EMDrive on a force-feedback thrust stand and achieved up to 720 mN of thrust with 1000 W microwave power with even higher Q factors compared to Shawyer. Most recently, Brady et al 13 tested the concept on a torsion balance at NASA with a µN resolution obtaining thrusts of 50 µN using only 20 W of RF power.…”
Section: Figure 1 Emdrive Conceptmentioning
confidence: 99%
“…Their experimental results, first reported in 2010, give a maximum force of 720 mN for an input microwave power of 2.5 kW. The force was measured on a pendulum test rig and the direction confirmed that it was the reaction force being measured, rather than the net force due to the difference in reflection forces at each end plate [2]. This is further confirmation that EmDrive is operating as a Newtonian machine, with a thrust generated in one direction and a reaction force in the opposite direction.…”
Section: Introductionmentioning
confidence: 74%